2019
DOI: 10.4103/ccd.ccd_898_18
|View full text |Cite
|
Sign up to set email alerts
|

Oral submucous fibrosis in a 5 year old child

Abstract: Oral submucous fibrosis (OSMF) is one of the potentially malignant disorders (PMDs), predominantly observed in adults with a habit of chewing areca nut. A rapid increase in the use of commercially available nicotine products, especially among the children and adolescents, is a reason for consequential concern. Nicotine products remain to be the chief etiological factor, which increases the susceptibility of the oral mucosa to different kinds of PMDs irrespective of the age groups. Here is a case report of oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“… 7 Jain et al 1 had conducted a review in 2019 with cases below 10 years of age and presented with a protocol for management of this premalignant condition in paediatric population. Talla et al 8 and Kariya et al 9 both reported a case of OSF in 5-year-old child. Recently, More et al 10 conducted an analysis of 36 cases of OSF in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Jain et al 1 had conducted a review in 2019 with cases below 10 years of age and presented with a protocol for management of this premalignant condition in paediatric population. Talla et al 8 and Kariya et al 9 both reported a case of OSF in 5-year-old child. Recently, More et al 10 conducted an analysis of 36 cases of OSF in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Our case report of OSMF in a 5-year-old girl draws attention to the increasing use of commercially available nicotine and areca nut products among children. The flavor and appealing packages are attracting the younger generation, and a lack of awareness of its adverse effects is resulting in a higher occurrence of PMDs among them [7]. The reason for the existence of such cases may be due to the spread of bad habits among children (tobacco use, alcohol drinking, chewing of betel quid containing areca nut, and solar rays), which prompts us to emphasize health education programs for children and early examination of the oral mucosa to register any possible disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Our case report of OSMF in a 5-year-old girl draws attention to the increasing use of commercially available nicotine and areca nut products among children. The flavor and appealing packages are attracting the younger generation, and a lack of awareness of its adverse effects is resulting in a higher occurrence of PMDs among them [7]. The reason for the existence of such cases may be due to the spread of bad habits among children (tobacco use, alcohol drinking, chewing of betel quid containing areca nut, and solar rays), which prompts us to emphasize health education programs for children and early examination of the oral mucosa to register any possible disorder.…”
Section: Introductionmentioning
confidence: 99%